Can Doppler ultrasound reduce hemorrhagic complications in ultrasound-guided percutaneous nephrolithotomy for solitary kidney stones? - Xiao, Bo; Zeng, Xue; Chen, Yang; Lin, Shen; Xu, Yangyang; Huang, Haiwen; Luo, Zhichao; Bai, Wenjie; Li, Jianxing (Frontiers in Surgery, 2025)
PurposeTo evaluate the role of Doppler ultrasound in reducing hemorrhagic events during percutaneous nephrolithotomy (PCNL) in solitary kidney calculi through a comparative analysis.Patients and methodsWe retrospectively reviewed the charts of urolithiasis patients who had undergone ultrasound-guided PCNL in our department from March 2021 to December 2024 and identified 76 eligible patients. Patients were stratified into two cohorts based on Doppler flow detection technology application: Group 1 (Doppler-mode, n = 29) and Group 2 (conventional mode, n = 47). Relevant patient characteristics, operative variables, and postoperative data were collected and analyzed, focusing on bleeding complications and stone-free rate (SFR).ResultsNo significant difference was found between the two groups regards to basic characteristics (gender, age, body mass index, stone size, pre-operative serum creatinine). The puncture time shows significant longer in Group 1 compared to Group 2 (173.1 ± 39.6 vs. 111.4 ± 29.9 s, p = 0.02). However, the hemoglobin loss reveals no significant difference between the two groups (17.5 ± 5.6 vs. 21.7 ± 6.3 g/L, p = 0.19). There were no significant differences in the operation duration (p = 0.47), transfusion rate (p = 0.15), postoperative creatinine (p = 0.80), overall complication (p = 0.07), final stone-free rates (p = 0.38) between the two groups.ConclusionDoppler flow technology fails to confer superior benefits in ultrasound-guided PCNL for solitary renal calculus, with no definitive necessity established for hemorrhage risk mitigation.